Analisis Perbandingan Performansi Algoritme Floyd-Warshall dan Algoritme Johnson untuk Penentuan Rute Terpendek pada Software Defined Network - Mohamad Ilham Firdaus; Rakhmadhany Primananda; Mochammad Hannats Hanafi Ichsan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
The growth of computer network technology has an impact on the high demand for network performance and increasingly control network complexity. Network performance can be affected by network management, one of which is routing protocol. On a conventional network, routing protocol configuration is inflexible, inefficient and needs to configure each network device. One of the solution for this problem is SDN (Software defined network). The programmable SDN control plane make it possible to implement routing application. This research uses two kind of shortest path algorithm those are Floyd-Warshall algorithm and Johnson algorithm. Both algorithms are implemented in ryu controller and mininet as SDN network simulator. Packet loss dan delay testing has no significant difference. In the packet loss testing Floyd-Warshall has an average of 2,33% compared to Johnson with an average of 2,48%. While the result of delay testing, the average delay of Floyd-Warshall is 4,08 ms compared to Johnson with an average of 4,02 ms. Convergence time testing, Johnson is faster when the number of switches 6 and 10. While Floyd-Warshall is better when the number of switches 14. In cpu usage testing, Johnson algorithm consumes more resources with an average of 23,84% compared to Floyd-Warshall algorithm with an average of 21,78%. While the result of memory usage of both algorithm equally consume 1,3% of memory.